التوقيع الإلكتروني كآلية لأمن و سلامة الوفاء الرقمي - عرعار, الياقوت (University of Eloued جامعة الوادي, 2020)
إنّ تطور تقنيات الاتصال الحديثة، بحيث أصبحت المعاملات تتّم من خلال شبكة الأنترنت، أظهر التوقيع الإلكتروني كاستجابة للمتغيرات التّي فرضتها التجارة الإلكترونية. إذ اقترن التوقيع الإلكتروني بشكل كبير بمجال المعاملات المصرفية والبنكية ، وخاصة فيما يتعلّق باستخدام بطاقات الائتمان الإلكتروني. يتّم الدفع الإلكتروني في بيئة مفتوحة وغير آمنة، حيث تتعدّد سبل اختراق الأمان و السرية بنظم الدفع الإلكتروني، مما يعرّض مصلحة المستهلك الإلكتروني للخطر، وسعيا لتحقيق مبدأ الثقة والأمان في الدفع الإلكتروني وحمايته من المخاطر ، أحاط المشرع التوقيع الإلكتروني بجملة من شروط الأمان ووضع له آلية آمنة لإنشائه وتنظيمه قانونيا من اعتباره توقيعا الكترونيا مؤمنا وله القوة الثبوتية. The development of modern communication technologies, so that transactions become through the Internet, has created the electronic signature in response to the changes imposed by electronic commerce, as the electronic signature has been closely associated with the field of banking and banking transactions, especially with regard to the use of electronic credit cards. Electronic payment takes place in an open and unsafe environment, where there are multiple ways to penetrate the security and confidentiality of electronic payment systems, which endangers the interests of the electronic consumer. In an effort to achieve the principle of trust and safety in electronic payment and protecting it from risks, the legislator surrounded the electronic signature with a set of safety conditions, and set up a safe mechanism for its creation and regulation legally from being considered a secure electronic signature and has the evidentiary power.
مجلد11، عدد3
Keywords: التوقيع الإلكتروني؛ التوقيع الرقمي؛ الدفع الإلكتروني؛ التصديق الإلكتروني؛ التشفير ؛الوسيط الإلكتروني ؛بطاقات الائتمان; electronic signature- digital signature; electronic payment; electronic certification; encryption; electronic medium ; credit cards